Ascorbate Peroxidase Activity of Aranda Broga Blue Orchid Protocorm-like Bodies (PLBs) In Response to PVS2 Cryopreservation Method - Khor Soo Ping; Rahmad Zakaria; Sreeramanan Subramaniam (Tropical Life Sciences Research, 2016)
Throughout the cryopreservation process, plants were exposed to a series of abiotic stresses such as desiccation and osmotic pressure due to highly concentrated vitrification solution. Abiotic stress stimulates the production of reactive oxygen species (ROS) which include hydrogen peroxide, superoxide radicals, and singlet oxygen. Higher production of ROS may lead to oxidative stress which contributes to the major injuries in cryopreserved explants. Antioxidant enzymes in plant such as ascorbate peroxidase (APX) can protect plants from cell damage by scavenging the free radicals. This study was determined based on APX enzyme activity of Aranda Broga Blue orchid’s protocorm-like bodies (PLBs) in response to PVS2 (Plant Vitrification Solution 2) cryopreservation treatments at different stages. PLBs that were precultured at 0.25 M sucrose for 3 days were subjected to vitrification cryopreservation method. Results obtained showed that the highest APX activity was achieved at PVS2 cryoprotectant treatment prior liquid nitrogen (LN) storage. This phenomenon indicating that accumulation of osmotic and dehydrating stress throughout the cryopreservation treatment resulted in oxidative burst which in turn leads to higher APX activity in order to control the excess production of ROS. To conclude, PVS2 treatment was revealed as the most detrimental step throughout cryopreservation treatment. Thus, this research also suggested that exogenous antioxidant such as ascorbic acid can be added throughout cryopreservation procedure especially at PVS2 treatment in the future experiments to aid in regrowth of cryopreserved explants by reducing oxidative stress.